A simplified approach to assess progressive collapse resistance of reinforced concrete framed structures. (15th October 2015) - Dat, Pham Xuan; Hai, Tan Kang; Jun, Yu
Highlights: A method for predicting progressive collapse resistance of RC building structures is presented. A beam hinge with lowest curvature ductility was chosen as the critical hinge. The ultimate flexural capacity is determined by yield-line analysis. This method is validated by 12 beam-slab sub-assemblage tests. It shows continuity of beam bottom reinforcement can mitigate progressive collapse. Abstract: Progressive collapse resistance of reinforced concrete (RC) building structures can be assessed by sudden column loss scenarios. Penultimate column loss is among the most critical scenarios since it leaves the affected beam-slab systems with lack of external lateral restraints. Under such accidental situation, flexural action in the double-span beams and slabs bridging over the removed column is experimentally identified as the main mechanism to redistribute the gravity loads, which is amplified by double span effect and dynamic effect. This paper presents a simplified approach for progressive collapse assessment of RC building structures subjected to a penultimate column loss. The collapse resistance is calculated based on an idealized elastic–plastic static response of a double-span beam-slab structure, which is constructed with ( i ) ultimate flexural capacity of the beam-slab structure that is determined by yield-line method of analysis and ( ii ) displacement ductility at the removed column position that is established based on curvature ductility of a critical connection touching on the affected area. The idealized static response is validated by experimental results of 12 beam-slab sub-assemblage tests. A simple step-by-step procedure together with worked examples are provided. Practical application of this approach and design recommendations for mitigating progressive collapse are discussed.